Synthesis of ZnO/CuO Nanocomposites Against Pathogenic Bacteria for Application in Food Packaging - แสงรุ่งเรือง ดร.พุทธิธร; ฟูเผ่า ผู้ช่วยศาสตราจารย์ ดร.ฐิตา; ภูหินกอง วีรชน (Journal of Food Health and Bioenvironmental Science, 2016)
Pathogenic bacterial infections from food via environment have been of considerable importance in recent years. The development of metal oxide material for antimicrobial food packaging is a potential way to reduce pathogenic bacteria in food. The ZnO and CuO have the unique properties to stop growth rates of pathogenic bacteria. This study sought to improve the synthesizing of ZnO/CuO nanocomposites via a co-precipitation method. The effect of inorganic salt addition and the precursor mole ratio of Zn2+ to Cu2+ were studied. The particle size and morphology were characterized by field emission scanning electron microscopy (FESEM) and energy-dispersive X-ray spectroscopy (EDX). The phase compositions were confirmed by X-ray diffraction infrared spectroscopy (XRD). The antimicrobial activity of the nanocomposite samples was investigated using a modified agar well diffusion method with Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) for Gram-negative and Gram-positive bacteria, respectively. The results indicate that well dispersion and mixing between ZnO and CuO in nanocomposite samples occurred. In the best condition, the nanocomposite samples showed an excellent inhibitory effect which was better than the commercial ZnO, nanoZnO and industrial ZnO and CuO. This study suggested that these ZnO/CuO nanocomposites can be potentially utilized in antimicrobial food packaging.